INCLUSION COFFEE SHOP AS THIRD PLACE: USER DESIGN AND EXPERIENCE PERSPECTIVE - Anggiani, Mona; Ayudya, Rr Diana; Sukmajati, Danto (Border: Jurnal Arsitektur, 2025)
Every human being shares the same fundamental needs, ranging from physiological to physical needs. After engaging in daily activities, individuals seek to relax and relieve stress through enjoyable experiences in comfortable environments. Commonly, these relaxing spaces are referred to as third places. One form of third place, as introduced by Oldenburg, is the coffee shop. As a third place, it is more than just a physical space—it holds deeper meaning. Today, coffee shops are frequently identified as third places; however, the criteria for a third place extend beyond mere spatial aspects. This study aims to explore whether coffee shops frequented by users can be considered third places from their perspective, and to identify the factors that influence this perception. The research adopts a qualitative approach by conducting interviews with participants. Data were analyzed using a descriptive narrative technique, presenting findings from observations and interviews. The results indicate that most users of a disability-friendly coffee shop consider it their third place for several reasons: the shop is inclusive and accessible to everyone; it features a unique and aesthetic design; it is strategically located, easily accessible, and near transportation hubs; it offers a calm, home-like atmosphere; it serves as a space for conversation; it provides comprehensive facilities; and it includes disability-friendly signage. This study is expected to serve as a foundation for the design and development of third places that accommodate the needs of deaf and hard-of-hearing individuals.